Features of Malevolent Creativity and its Prevention in Adolescents in the Modern Socio-Political Context - N.V. Meshkova; S.N. Enikolopov; M.N. Bochkova; I.A. Meshkov (Психология и право)
The article presents the results of a series of studies on the influence of socio-political conditions — the modern context and the pre-covid period, on the manifestation of malevolent creativity in behavior that harms other people. The sample consisted of adolescents (N=52, 19 - boys; Age = 16.0 years); samples of cadets (N=96, 72 - boys; М = 15.4 years), cadets-students (N=204, 152 — men; M = 19.3), psychology students (N=50, 3 - men; M = 20.4). Hypotheses about differences in different contexts were tested: 1. in the levels of malevolent creativity (MC), 2. in the relationship MC with personal characteristics and between personal characteristics, 3. the presence of age-related characteristics of MC that do not differ in different socio-political conditions. A battery of questionnaires was used: NEO-FFI, BPAQ-24, “Behavioral features of antisocial creativity”, moral identity, “Tolerance Index” and a developed questionnaire with statements about the presence/absence of attention to the news about the situation in Russia and the world and the sources of this information. The results obtained confirmed the hypotheses put forward. It is noted that the existing limitations in the study made it possible to identify not only the features of antisocial creativity in adolescents in different socio-political conditions, but also features related to the professional context (civil professions and law enforcement agencies), allowing them to be taken into account in the prevention of antisocial creativity in the modern socio-political context.